Establishment of tissue culture and transformation protocol for tropical corn (Zea mays L.) inbred lines - Matazu, Nasiruddeen Umar (2015)
Traditional crop improvement alone is insufficient to meet the growing demand of maize hence the need for genetic transformation. Genetic transformation of maize is dependent on the formation of reliable and efficient plantlet regeneration system. However, previously established protocols for tissue culture and genetic transformation are based on maize model genotypes. Hence there is a need to develop a new protocols for these new lines since it’s a known fact in vitro cultures is majorly dependent genotype. The major objectives of this study was to establish a reliable tissue culture and transformation protocols for some selected tropical CIMMYT maize lines (CML 406, CML 419, CML 425 and CML 427). Studies performed to evaluate the competence of these lines in responding to in vitro stimulus revealed callus initiation, proliferation and maintenance was accomplished in N6 media augmented with 9 μM 2,4-D and 200 mg/L casein hydrolysate, or 5 μM dicamba and 200 mg/L casein hydrolysate in all the genotypes. CML 427 has the highest response with 91.33% followed by CML 419 with 86.67%. The lowest callus induction and proliferation frequency was recorded in CML 425 with 41.67% using 17 days after pollination (DAP) immature zygotic embryo (IZE). Addition of 0.015 mg/L AgNO3, 0.02 mg/L Ag2SO4 and 4.12 g/L -aminobutyric acid to culture media have significantly increased the formation of embryogenic callus. Studies of callus growth pattern showed all but CML 419 genotype attained maximum growth at 4th week while CML 419 have maximum growth at 3rd week of culture. Complex organic compounds which included yeast extract, potato extract, coconut water and casein hydrolysate have significantly enhanced callus growth when both fresh and dry weights were measured. Indirect regeneration via organogenesis was accomplished in CML 419 and CML 427 in MS media containing 1 mg/L kinetin, 2 mg/L BAP and 2 mg/L TDZ in separate experimental units. Regeneration efficiencies in these media were found to be 12% and 16.4%; 7.8% and 6.2%; and 3.5% and 4.6% for CML 419 and CML 427 respectively. Both somatic embryogenesis and organogenesis are genotype dependent. Callus transformation was achieved using Agrobacterium tumefaciens strains LBA 4404 harboring pCAMBAIA1304 vector containing (mgfp5-gusA-His6 fusion). Fluorescence microscopy, GUS staining, and PCR amplification of gfp, gus and hpt II genes indicated that both GFP and GUS were expressed in the callus. Transformation efficiency was found to be 1.33% and 1.67% for CML 419 and CML 427 respectively. Antioxidative enzyme assays suggest that glutamate dehydrogenase, glutathione reductase, lipid peroxidation and superoxide dismutase activities are significantly (p≤ 0.05) higher in test samples than the control. On the other hand, there is no statistically significant difference in catalase and ascorbate peroxidase activities between the test groups and the control. NMR-based metabolomic studies revealed metabolic differences at different stages of development. The unique compounds discovered in both embryogenic samples are , inositol, choline, proline, -glucose,asparagine, acetoacetate, ascorbate, aspartate, and phenylalanine. The common metabolites in both embryogenic and organogenic samples from both lines are -glucose, sucrose, asparagine, aspartate and choline. The major importance of these findings is that organogenic and embryogenic competence in maize is attributed to genotype and cells undergoing embryogenesis and organogenesis evolved special organelles that whose functions remain obscure. Secondly, metabolic data generated could be very useful in understanding these vital processes. These have impressive implications in the basic research especially in cellular and developmental biology. Moreover, this information could be used to identify potential biomarkers, identification gene functions and in drug discovery among others.